Coronary Artery Aneurysm Differs From Coronary Artery Ectasia: Angiographic Characteristics and Cardiovascular Risk Factor Analysis in Patients Referred for Coronary Angiography. (October 2017) - Luo, Yu; Tang, Jiani; Liu, Xu; Qiu, Jianping; Ye, Zi; Lai, Yan; Yao, Yian; Li, Jimin; Wang, Xiaodong; Liu, Xuebo
The differences in angiographic characteristics and cardiovascular (CV) risk factors between coronary artery aneurysm (CAA) and coronary artery ectasia (CAE) have not been compared systematically. Of 10 876 patients undergoing coronary angiography, patients with CAA (n = 85) and CAE (n = 51) were screened. The prevalence of CAA was greater than that of CAE ( P < .05). The right coronary artery was the most involved (70.6%) in CAE compared with left circumflex (52.9%) and left anterior descending (41.2%). Coronary artery aneurysm coexisted with coronary artery disease (CAD) more frequently than CAE ( P = .002), and the modified Gensini score of CAA was also higher than that of CAE ( P < .001). The average maximum diameter was smaller, and corrected Thrombolysis in Myocardial Infarction (TIMI) frame count was lower in CAA than CAE in all 3 coronary arteries ( P < .001). Multivariate analysis showed that hyperlipidemia ( P = .02), smoking ( P = .04), and family history of CAD ( P = .02) were the independent variables most strongly associated with CAA, but not CAE. This study suggests that there are significant differences in coronary angiographic characteristics and CV risk factors between CAA and CAE.